Enhanced TNFα and oxidative stress in patients with heart failure: effect of TNFα on platelet O2- production - Biase, Luciano De; Pignatelli, Pasquale; Lenti, Luisa; Tocci, Giuliano; Piccioni, Fabiana; Riondino, Silvia; Pulcinelli, Fabio M.; Rubattu, Speranza; Volpe, Massimo; Violi, Francesco (Thrombosis and Haemostasis, 2003)
Experimental studies have suggested that TNFα, a pro-inflammatory cytokine, may contribute to the deterioration of cardiovascular function through various mechanisms, including the generation of reactive oxygen species. It has not yet been demonstrated whether TNFα has prooxidant activity in patients with heart failure, and what the mechanism eventually resulting in this effect are.We analyzed 42 patients (38 men and 4 women, aged 26 to 74 years) with heart failure, secondary to idiopathic dilated car-diomyopathy (n=21), coronary artery disease (n=15), and valve disease (n=6), and 20 controls (18 men and 2 women, aged 49 to 67 years). Ten patients were in class I,9 in class II,15 in class III and 8 in class IV according to NYHA Classification. Blood samples were obtained from each patient to evaluate basal and collagen-induced platelet O2- production, and plasma TNFα. In vivo results showed increased platelet O2- production and plasma TNFα levels in NYHA class III-IV compared with that in controls or in NYHA I-II (p<0,001); platelet O2- production correlated significantly (R=0,6; p<0,01) with TNFα plasma levels. In vitro studies showed TNFα dose-dependently (5-40 pg/ml) induced platelet O2- production, and that this effect was significantly inhibited by its specific inhibitor, WP9QY (1 μM); aspirin (100 μM), AACOCF3, a specific PLA2 inhibitor (14 μM), and DPI, an inhibitor of NADPH oxidase, significantly inhibited TNFα-mediated platelet O2- production.This study suggests that in patients with heart failure, enhanced platelet O2- production is mediated by TNFα via activation of arachidonic acid and NADPH oxidase pathways.
Keywords: Platelets; heart failure; oxidative stress; TNF alpha